MICROCLIMATE PARAMETERS AT DIFFERENT WAYS OF KEEPING FATTENING YOUNG STOCK - Пікула, Оксана (Modern engineering and innovative technologies, 2022)
The microclimate in the livestock building plays a significant role in the maintenance of farm animals. The data on growing and fattening of young cattle are disclosed in detail, where among the factors that affect beef production are zoohygienic conditio